1998
DOI: 10.1097/00004694-199805000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Between 1985 and 1996, our Service treated 18 cases of osteochondritis dissecans of the talus in children and adolescents. The lesion is more frequent during childhood than previously thought. Different theories about the etiology of the lesion and the various treatments used are discussed. The outcome was satisfactory in most cases. We consider that, with the exception of type IV Berndt and Harty lesions, preliminary treatment should be conservative, which gave good results in our study. Surgical treatment sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
1
6
1
Order By: Relevance
“…Due to the small sample numbers, statistically significant conclusions could not be reached based on lesions of the trochlea (3 of 4), tibial plateau (1 of 1), and patella (1 of 3) that progressed to surgery. However, our results indirectly support the findings of several authors who, though not necessarily documenting a lower rate of surgery in MFC lesions, have noted either a greater rate of healing in MFC lesions 9 or better clinical results in classic MFC lesions in the central or lateral MFC 21 as opposed to lesions elsewhere in the knee.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Due to the small sample numbers, statistically significant conclusions could not be reached based on lesions of the trochlea (3 of 4), tibial plateau (1 of 1), and patella (1 of 3) that progressed to surgery. However, our results indirectly support the findings of several authors who, though not necessarily documenting a lower rate of surgery in MFC lesions, have noted either a greater rate of healing in MFC lesions 9 or better clinical results in classic MFC lesions in the central or lateral MFC 21 as opposed to lesions elsewhere in the knee.…”
Section: Discussionsupporting
confidence: 91%
“…The literature is quite variable regarding progression to surgery for ankle OCD, with a surgical intervention rate between 19% and 58% in multiple studies. 11 , 21 , 32 Looking specifically at children, Letts et al 32 found a surgical intervention in only 1 of 5 in children under the age of 12 years, Higuera et al 21 found a 33% surgical intervention rate in their study of pediatric ankle OCD, and the 20-year follow-up study by Bauer et al 11 on ankle OCD in a mixture of children and adults found that only 1 of 5 children had surgery. As with knee OCD, surgical progression for ankle OCD did not significantly differ based on either sex and, in contrast to knee OCD, location within the ankle did not seem to correlate with nonoperative treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive, excessive compression of the subchondral bone caused by stress and trauma can result in OCD [ 2 ]. The condition wherein compression force is applied to the talar posterior calcaneal articular surface is similar to that of a fracture of the talar lateral process.…”
Section: Discussionmentioning
confidence: 99%
“…It is also called an osteochondral lesion. Repetitive, excessive compression of the subchondral bone caused by stresses or trauma can result in OCD [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ischemia of the subchondral bone causes separation of the fragment from the underlying bed. Osteochondral lesions of the talus occur anterolaterally, but posteromedial lesions are more common and account for 74% of these lesions 13. Central lesions are rare.…”
Section: Talar Osteochondral Injuriesmentioning
confidence: 99%